INFLUENCE OF THE WATER DISTRIBUTION UNIFORMITY AND IRRIGATION DEPTH ON THE YIELD OF IRRIGATED BEAN CROP - Mantovani, Everardo C.; Faccioli, Gregório G.; Leal, Brauliro Gonçalves; Soares, Antonio Alves; Costa, Luis Claudio; Freitas, Paulo Sergio L. (IRRIGA, 2009)
INFLUENCE OF THE WATER DISTRIBUTION UNIFORMITY AND IRRIGATION DEPTH ON THE YIELD OF IRRIGATED BEAN CROP Everardo C. Mantovani1; Gregório G. Faccioli2; Brauliro Gonçalves Leal3;Antônio Alves Soares1; Luis Cláudio Costa1; Paulo Sérgio L. Freitas4 1Departamento de Engenharia Agrícola, Universidade Federal de Viçosa, MG everardo@ufv.br 2Núcleo de Estudos e Pesquisas do Nordeste, Universidade Federal de Sergipe, São Cristovão, SE 3Intec Consultoria e Assessoria Ltda, Viçosa, MG 4Departamento de Agronomia, Universidade Estadual de Maringá, Maringá, PR 1 ABSCTRACT This study aimed to evaluate the influence of the water distribution uniformity and three irrigation depths on the production variables for the bean crop, using a conventional sprinkler irrigation system, during the winter season. The treatments consisted of three irrigation depths and two uniformity levels of water distribution represented by the Christiansen uniformity coefficient (CUC). In the treatments L1A and L1B a sufficient water depth was applied to raise the soil water content to field capacity. The distribution uniformities (CUCs) were higher and lower than 80%, respectively. In treatments L2A and L3A, and L2B and L3B, the applied water depths corresponded to 50% and 150% of that applied to the LIA treatment. Because of rainfall events until the sampling date, no significant differences at 5% probability were found among treatments, when the variables were: leaf number, leaf area and dry matter. The F test for the contrast among the treatments with high and low uniformity was significant at 5% probability, when using 50% replacement of the water depth required by the crop. Significant differences were observed at 5% probability for pod number per plant among the treatments, when using 150, 100 and 50% replacement of the water depth required by the crop KEYWORDS: irrigation uniformity, sprinkler irrigation, yield. MANTOVANI, E. C.; FACCIOLI, G. G.; LEAL, B. G.; SOARES,A. A.; COSTA, L. C.; FREITAS, P. S. L. INFLUÊNCIA DA UNIFORMIDADE DE DISTRIBUIÇÃO DE ÁGUA E LÂMINA DE IRRIGAÇÃO NA PRODUTIVIDADE DO FEIJÃO 2 RESUMO O presente trabalho teve como objetivo avaliar a influência da uniformidade de distribuição de água e de três lâminas de irrigação nas variáveis de produção da cultura do feijão, utilizando um sistema de aspersão convencional, no período de inverno. Os tratamentos constaram de três lâminas de irrigação e dois níveis de uniformidade de distribuição de água, representados pelo coeficiente de uniformidade de Christiansen (CUC). Nos tratamentos L1A e L1B foi aplicada uma lâmina de água suficiente para elevar a umidade do solo à capacidade de campo, com uniformidade de distribuição (CUC) maior e menor que 80%, respectivamente. Nos tratamentos L2A e L3A, e L2B e L3B as lâminas aplicadas foram, respectivamente, 50% e 150% da lâmina aplicada no tratamento L1A. Não existiram diferenças significativas, a 5% de probabilidade, nos tratamentos para seguintes variáveis: número de folhas, área foliar e matéria seca, em razão das chuvas ocorridas até a data da amostragem. O teste F para o contraste entre os tratamentos de alta e baixa uniformidade com 50% de reposição da lâmina requerida pela cultura foi significativo a 5% de probabilidade. Observou-se diferenças significativas, a 5% de probabilidade entre os tratamentos com 150, 100 e 50% de reposição da lâmina requerida pela cultura, para o número de vagens por planta. UNITERMOS: Uniformidade de irrigação, irrigação por aspersão, produtividade.